PENGGUNAAN FOTO UDARA DALAM PENILAIAN KERUSAKAN TAJUK AKIBAT EKSPLOITASI HUTAN - Ishak Sumantri; Wesman Endom (Jurnal Penelitian Hasil Hutan, 1988)
An investigation of the impact of logging operations on crown damage by using the aerial photograph  of forest  areas of PT. INHUTANI II in Pulau Laut, South Kalimantan was carried out.The results of the investigation lead to the following conclusions:1.  Panchromatic   black and white  aerial photograph of 1:20.000 scale is good  enough  to  use for  evaluating  the damage of dominant and codominant crowns and crown  closure of the trees. It is found that  the crown of  11 trees/ha  were damaged, consisted of 9 tree crowns were damaged partially and  2  tree crowns  were damaged  totally.2.   Steeper terrains  caused  larger decrease  of  crown closure  of  the  trees. On  the slope  of  0-15%,  25-45% and 45%  and above, the  crown  closure  reductions   were  61%, 76%  and 80%,  respectively